Plasma oxidative stress level of IgA nephropathy in children and the effect of early intervention with angiotensin-converting enzyme inhibitors. (May 2016) - Pei, Yuxin; Xu, Yuanyuan; Ruan, Jingwei; Rong, Liping; Jiang, Mengjie; Mo, Ying; Jiang, Xiaoyun
Aim: The purpose of this study was to investigate the change of the plasma oxidative stress level in children with IgA nephropathy (IgAN) and analyze its relativity to the clinical and pathological classification. To discuss the early effects of angiotensin-converting enzyme inhibitors (ACEIs) on the plasma oxidative stress level in children with IgA nephropathy. Methods: Thirty-eight children with IgAN were divided into groups according to their clinical features, pathologic grades, and treatments. Twenty healthy children were included in the control group. Results: The plasma level of advanced oxidation protein products (AOPPs), malonaldehyde (MDA), and superoxide dismutase (SOD) were detected. The plasma level of oxidative stress was significantly increased in the IgAN group, including a higher plasma level of AOPP and MDA and a lower plasma level of SOD. After treatment, the plasma level of oxidative stress was significantly decreased in the ACEI group. Conclusions: The children with IgAN had an increase in the plasma level of oxidative stress, expressed as an increased plasma level of AOPP and MDA and a decreased plasma level of SOD. Oxidative stress was associated with the progression of IgAN in children. Early treatment with ACEI therapy can significantly reduce the plasma level of oxidative stress in children with IgAN.